Old Dog New Tricks; Revisiting How Stroke Modulates the Systemic Immune Landscape - Krishnan, Siddharth; Lawrence, Catherine B. (Frontiers in Neurology, 2019)
Infections in the post-acute phase of cerebral ischaemia impede optimal recovery by exacerbating morbidity and mortality. Our review aims to reconcile the increased infection susceptibility of patients post-stroke by consolidating our understanding of compartmentalised alterations to systemic immunity. Mounting evidence has catalogued alterations to numerous immune cell populations but an understanding of the mechanisms of long-range communication between the immune system, nervous system and other organs beyond the involvement of autonomic signalling is lacking. By taking our cues from established and emerging concepts of neuro-immune interactions, immune-mediated inter-organ cross-talk, innate immune training and the role of microbiota-derived signals in central nervous system (CNS) function we will explore mechanisms of how cerebral ischaemia could shape systemic immune function. In this context, we will also discuss a key question: how are immune requirements critical for mediating repair of the ischaemic insult balanced by the need for anti-microbial immunity post-stroke, given that they are mediated by mutually exclusive immune networks? Our reformed understanding of the immune landscape post-stroke and novel mechanisms at play could guide targeted therapeutic interventions and initiate a step-change in the clinical management of these infectious complications post-stroke.